Insulin pump therapy of type 1 diabetes mellitus in children and adolescents in the Moscow region - Elena Efimovna Petryaykina; Olga Viktorovna Dukhareva; Irina Georgievna Rybkina; Ekaterina Alexandrovna Pronina; Tatiana Dmitrievna Mikhaylova; Irina Viktorovna Garyaeva; Eleonora Tavanovna Mandzhieva; Igor Eduardovich Volkov; Natalya Mikhailovna Grenkova (Сахарный диабет)
Aim. To assess dynamics of glycated hemoglobin levels and insulin doses per kg bw in children and adolescents with poorly controlled type 1 diabetes mellitus using insulin pumps. Materials and methods. Retrospective analysis of HbA1c levels and insulin doses per kg bw in children aged 2-17 years with DM1 (mean duration 5.3?3.1) before and 18 months after onset of insulin pump therapy (Medtronic Minimed 712 and 722) with a short-acting insulin analog Novopramid (Novo Nordisk) or Humalog (Ely Lilly) given to 55 (52,4%) and 50 (47,6%) of the patients respectively. НbА1с level and mean daily insulin dose per kg bw were determined when a patient visited the doctors office every 3 months. Results. Insulin pump therapy in patients with initially poorly controlled DM1 resulted in a decrease of HbA1c from 9.8?0.8 to 7,8?0,5% within 18 months after its beginning (p